Clinical and histological profile of gestational trophoblastic disease in the state of Piauí (Research, Society and Development, 2022)
This work aims to trace the clinical and histological profile of molar pregnancy in a tertiary maternity in the state of Piauí. This is a cross-sectional observational study with a quantitative approach. We analyzed 90 medical records of pregnant women with GTD between 14 and 50 years old admitted to a tertiary maternity hospital in Piauí between January 2016 and December 2019. Inclusion and exclusion criteria were used to select the records. A survey of variables was carried out, such as age, parity, beta HCG, clinical status, gestational age, method of emptying, histopathology, follow-up, contraceptive method and evolution. The results showed that only 0.6% of the women followed up during the study period developed GTD, the most expressive age group was between 20 and 30 years old. Regarding the histopathology, 73% were diagnosed with complete hydatidiform mole. Regarding the evolution of the disease, 73% of the patients progressed to cure, 7% developed GTN, 6% are in progress and 13% of them did not complete the follow-up. Therefore, the study was of great importance regarding the clinical and histological profile of women with GTD, since these factors are closely related to the evolution of the disease. The number of patients who did not complete the treatment is low, but it cannot be ignored, therefore, carrying out an active search for patients who did not complete the follow-up is essential. As limitations of this study, there is a probable loss of follow-up of some women, especially during the period of the covid-19 pandemic.